2D Graphene/MnO Heterostructure with Strongly Stable Interface Enabling High‐Performance Flexible Solid‐State Lithium‐Ion Capacitors. (6th May 2022) - Liu, Wenjie; Zhang, Xiong; Xu, Yanan; Wang, Lei; Li, Zhao; Li, Chen; Wang, Kai; Sun, Xianzhong; An, Yabin; Wu, Zhong‐Shuai; Ma, Yanwei
Abstract: The delicate structural engineering is widely acknowledged as a powerful tool for boosting the electrochemical performance of conversion‐type anode materials for lithium storage. Here, a general electrostatic self‐assembly strategy is proposed for the in situ synthesis of MnO nano‐cabbages on negatively charged reduced graphene oxide (rGO/MnO). The strong interfacial heterostructure and robust lithium storage mechanism related to fast Li + diffusion kinetics and high Li‐adsorption ability of rGO/MnO heterostructure are confirmed through operando experimental characterizations and theoretical calculation. Owing to the rapid charge transfer, enriched reaction sites, and stable heterostructure, the as‐synthesized rGO/MnO anode delivers a high capacity (860 mAh g −1 at 0.1 A g −1 ), superior rate capability (211 mAh g −1 at 10 A g −1 ), and cycle stability. Notably, the as‐assembled flexible pouch cell of activated carbon//rGO/MnO solid‐state lithium‐ion capacitors (LICs) possesses an exceptional energy density of 194 Wh kg −1 and power density of 40.7 kW kg −1, both of which are among the highest flexible solid‐state LICs reported so far. Further, the LICs possess an ultralong life span with ≈77.8% retention after 10 000 cycles and extraordinary safety, demonstrative of great potential for practical applications. Abstract : A general electrostatic self‐assembly strategy is proposed for synthesizing nano‐cabbages like MnO anchored on reduced graphene oxide (rGO/MnO). Benefited from the strong interfacial interactions, fast Li + diffusion kinetics, and high Li‐adsorption ability, the rGO/MnO heterostructure possesses impressive capacity and rate performances. Further coupled with activated carbon to assemble high‐performance flexible solid‐state lithium‐ion capacitors, demonstrating its feasibility for practical applications.